Highly Simplified and Bandwidth‐Efficient Human Body Communications Based on IEEE 802.15.6 WBAN Standard. Issue 6 (1st December 2016) - Kang, Tae‐Wook; Hwang, Jung‐Hwan; Kim, Sung‐Eun; Oh, Kwang‐Il; Park, Hyung‐Il; Lim, In‐Gi; Kang, Sung‐Weon
Abstract : This paper presents a transmission method for improving human body communications in terms of spectral efficiency, and the performances of bit‐error‐rate (BER) and frame synchronization, with a highly simplified structure. Compared to the conventional frequency selective digital transmission supporting IEEE standard 802.15.6 for wireless body area networks, the proposed scheme improves the spectral efficiency from 0.25 bps/Hz to 1 bps/Hz based on the 3‐dB bandwidth of the transmit spectral mask, and the signal‐to‐noise‐ratio (SNR) by 0.51 dB at a BER of 10 − 6 with an 87.5 % reduction in the detection complexity of the length of the Hamming distance computation. The proposed preamble structure using its customized detection algorithm achieves perfect frame synchronization at the SNR of a BER of 10 − 6 by applying the proposed pre‐processing to compensate for the distortions on the preamble signals due to the band‐limit effects by transmit and receive filters.